Ankle fractures and rapidly progressing osteoarthrosis of the ankle joint: prevention and treatment - Omelchenko, Taras (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
A complex of medical measures, aimed at prevention of the development and progression of post-traumatic osteoarthrosis, was developed. This complex included early surgical treatment with reposition of fragments and stable functional osteosynthesis, both under image converter control. Postoperatively, besides general drug treatment and rehabilitation system, we used S-adenosyl-L-methionine (SAM-e®) together with an intra-articular injection of a combined preparation of hyaluronic acid and succinate, which have antioxidant, stabilizing, chondrocytes-stimulating and chondroprotective properties. Results of this treatment in 50 patients with intra-articular fractures of their ankle joint were analysed. A high efficacy of the above method for preventing the development and progression of osteoarthrosis, reducing pain syndrome and increasing the functional activity of the patients was proved.